Pengaruh Marketing Mix Terhadap Keputusan Menabung Dengan Reputasi Sebagai Variabel Intervening Pada Bank BNI KCP. Univ. Jember - Alfiatin Alfiatin; Yuniorita Indah Handayani; Muhaimin Dimyati (STIE Mandala Jember, 2021)
This study aims to examine whether there is a product, price, place and promotion influence on saving decisions through reputation as an intervening variable. The population in this study are bank customers who have joined more than one month to more than two years BNI kcp Bank. Univ. Jember The sampling technique in this study uses the accidental sampling approach. The number of samples is 100 respondents. The analysis method used is the path analysis method using SPSS 22 software. The results of this study show that the marketing mix has an effect on reputation, and reputation has an effect on saving decisions. Products, prices and promotions affect the decision to save while the place / location has no effect on the decision to save. From the results of the path analysis, reputation is only able to be an intervening variable on the place / location variable on saving decisions. Keywords: Product, Price, Place, Promotion, Reputation, Savings Decision